Temporomandibular joint dysfunction : a practitioner's guide - Isberg, Annika (Isis Medical Media, 2001)
Temporomandibular joint (TMJ) dysfunction is a very common, yet frequently misdiagnosed, problem. It\'s essential to have a thorough understanding of not only anatomy and physiology, but also the broad spectrum of normal structures and possible deviations from the norm. In this abundantly illustrated new book, the author guides you through a wide range of causes and symptoms of joint dysfunction in both children and adults. This highly practical guide covers everything from normal TMJ function, pain, and joint sounds, to trauma, infectious arthritis, and inflammatory diseases. An extensive discussion of the use of radiography, arthroscopy, videofluroscopy, CT and MRI in detecting and treating TMJ makes this text highly practical and ideal for daily practice.
Keywords: syndrom temporomandibulárního kloubu; zubní lékařství; ortodoncie; Temporomandibular Joint Dysfunction Syndrome